Improving 1,2-Ethylene Dichloride Yield and Purity with Reducing Carbon Emissions from Ethylene through Waste Treatment Method Modification - Saputra, M. Syauqi Finardhy; Azhar, Rheka Fauzan; Ramadhani, Try; Dodi, Vares (Journal of Chemical Engineering Research Progress, 2025)
1,2-ethylenedichloride (EDC) is a chemical compound used widely in industry. This study aims to develop a modified process for EDC production through direct chlorination and oxychlorination methods to improve mass efficiency, establish an environmentally friendly plant, and produce high purity products. Conceptual process simulation was conducted using Aspen HYSYS, with energy consumption and carbon emission analysis using Aspen Energy Analyzer. Process modifications included a new separation system incorporating a flash drum separator, liquid-liquid extraction, and reboiled absorber to achieve more high yield from 71796.84 kg/h to 71859.39 kg/h and purity from 94% to 99.05% and. The results showed improved efficiency purity and yield with reduced carbon emissions from 67680 kg/h to 14170 kg/h, with the potential for industrial sustainability through feedstock optimization and reduced environmental impact. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).